Functional equations and modelling in science and engineering - Catillo, Enrique (Monographs and textbooks in pure and applied mathematics)
Provides engineers and applied scientists with some selected results of functional equations and their applications, with the intention of changing the way they think about mathematical modelling. Many of the proofs are simplified or omitted, so as not to bore or confuse engineers. Functional equati